A new, long-standing misidentified species of Psychrophrynella Hedges, Duellman & Heinicke from Departamento Cusco, Peru (Anura: Strabomantidae) - de La Riva, Ignacio; Chaparro, Juan C.; Padial, José M. (Zootaxa, 2008)
We present the description of a new species of the recently described genus Psychrophrynella. Hitherto, frogs of this new species were traditionally misidentified as Phrynopus peruvianus. The new species is known only from elevations of 3270–3450 m in the vicinity of the type locality in the Cordillera de Paucartambo, Departamento Cusco, Peru. It is unique within Psychrophrynella in having a marked, oblique inner tarsal tubercle. The geographically closest species Psychrophrynella bagrecito Lynch, also possesses a tarsal tubercle.